The Effect of Ration Contain Different Level of Protein and Energy on The Body Composition of Bali Cattle Heifers - I. C., Tungga; Suryani, N. N.; Sarini, N. P. (Jurnal Peternakan Tropika, 2018)
This study aims to find out the effect of different levels protein and energy rations given to the body composition of bali cattle heifers. This research was conducted at Cattle Farm in Belok Sidan Village, Petang District, Badung Regency for 3 months. A total of 12 heifers in this study, were use and they were divided into three groups by their weights. Randomized block design (RBD) was used for experimental design. There were four different rations given those groups; Those rations were A consisted of 12% crude protein and 2000 kcal ME/kg of energy; B (13% crude protein and 2100 kcal ME/kg of energy); C (14% crude protein and 2200 kcal ME/kg of energy) and D (15% crude protein and 2300 kcal ME/kg of energy). Variables observed were water (%), fat (%), protein (%) and fat retention (g/e/h). This study showed that water and protein of the body were not affected (P>0,05) by above treatment of the body, on the contrary to the fat content and fat retention. The highest body fat and fat retention obtained in treatment D were about 20,33% and 85,81 g/e/h. Hence, it can be concluded that ration contain 12% to 15% crude protein and 2000 to 2300 kcal ME/kg metabolic energy not affected water, and protein of the body. This results were still in the range of the standard recommended. Where as 39,8%-77,6% for the body water and 12,4%-20,6% for the body protein. 15% of crude protein and 2300 kcal ME/kg of energy given resulted in the highest body fat and retention rates of 20,33% and 85,81 g/e/h, respectively. Key words : body composition , protein and energy levels , bali cattle heifer